PENINGKATAN KOMPETENSI PROFESIONAL GURU MELALUI PELATIHAN KAHOOT DI SDN 01 KULU KECAMATAN KARANGANYAR KABUPATEN PEKALONGAN TAHUN PELAJARAN 2020/2021 - Lucia Prabawati Prasetyaningsih (Universitas Ngudi Waluyo, 2022)
The purpose of this study was to determine the increase in the professional competence of SDN 01 Kulu teachers in using the Kahoot program in learning activities through training to make Kahoot. This research uses School Action Research (PTS), in school action research, principals can reflectively analyze, synthesize, what is being done in schools. This research was conducted in two cycles. Each cycle includes planning (plan), action (action), observation (observation), and reflection (reflection). Methods of collecting data with observation and documentation methods. There was an increase in teacher competence in making quizzes using Kahoot. Before giving the action, the teacher's ability was only able to reach 27% enough and 73% less. After being given action in the form of training activities to make online questions using googleform, teacher competence increased in the first cycle to 46% in the sufficient category and 54% of teachers in the good category, and in the second cycle to 73 who participated in the training in the good category, and 27% of teachers in the good category. sufficient category and overall the assessment aspects have been in good criteria. So it can be concluded that there is an increase in the professional competence of teachers through Kahoot training at SDN 01 Kulu, Karanganyar District, Pekalongan Regency.